2013
DOI: 10.1159/000351339
|View full text |Cite
|
Sign up to set email alerts
|

A Surgical Model for Isolating the Pig Liver in vivo for Gene Therapy

Abstract: Several studies report results that suggest the need of vascularization blocking for efficient gene transfer to the liver, especially in nonviral gene therapy. In this study, we describe a surgical strategy for in vivo isolation of the pig liver, resulting in a vascular watertight organ that allows the evaluation of several gene injection conditions. The hepatic artery and portal, suprahepatic and infrahepatic cava veins were dissected. Then, liver vascularization was excluded for 5-7 min. In that time, we fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…In this context, high flow rates (40-100 ml/s) resulted in low transfection efficiency, whereas, in our experience [28], lower injection flow rates (10-20 ml/s) resulted in transcription indexes equivalent to genes with low-intermediate expression activity. These findings agree with the efficacy of gene transfer to watertight human liver segments [20], employing mild injection flow rates (10 ml/s).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In this context, high flow rates (40-100 ml/s) resulted in low transfection efficiency, whereas, in our experience [28], lower injection flow rates (10-20 ml/s) resulted in transcription indexes equivalent to genes with low-intermediate expression activity. These findings agree with the efficacy of gene transfer to watertight human liver segments [20], employing mild injection flow rates (10 ml/s).…”
Section: Discussionmentioning
confidence: 56%
“…After achieving efficient gene transcription following gene transfer in the surgically isolated pig liver in vivo [28], we aimed to establish a minimally invasive procedure for liver isolation by endovascular catheterization. Endovascular procedures offer advantages in terms of their potential clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…While effective and safe in small animals, the major challenge is in applying this simple procedure in human gene therapy. For this purpose, a few groups have reported some success in rabbits and small pigs (<20 kg) [8], [9], [21][26]. We have reported catheter-based, regional hydrodynamic gene delivery to transfer reporter plasmids to a specific region of a target organ by inserting the catheter into a selected blood vessel [8], [9], [11].…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, the complete liver vascularization of the pig can be occluded up to 20 min without neither hepatic injury nor systemic damage [52]. Considering this fact, Carreño et al [50] described in pigs a surgical procedure to completely exclude liver vascularization 'in vivo' and perform hydrodynamic gene delivery, targeting the entire organ. A complete midline laparotomy was carried out, exposing all the abdominal organs.…”
Section: Clinical Translation Of Hydrodynamic Gene Therapymentioning
confidence: 95%
“…Aiming to achieve localized high pressure without affecting the systemic circulation, they proposed individualizing the lobe by employing catheters with balloon and ligation. Although most of the authors suggested blood pressure to be the most important feature of hydrodynamic injection for efficient gene transfer, others have pointed other characteristics such as impulse [49] and flow rate [50,51] to be relevant. However, nearly all authors agree to the need for isolating target areas or the entire liver to improve the procedure efficiency.…”
Section: Clinical Translation Of Hydrodynamic Gene Therapymentioning
confidence: 99%